The Effect of Cooperative Education and Entrepreneurship Training on Credit-Union Members’ Welfare - Cornelius Timang; Baktiar Baktiar; Muh. Haekal Yunus (Penerbit Goodwood, 2026)
Purpose: This study examines the impact of cooperative education and entrepreneurship training on member welfare in the Sauan Sibarrung Credit Union in Tana Toraja. Does Education and Training at Credit Union Sauan Sibarrung have a positive impact on members' welfare? The Sauan Sibarrung Credit Union Cooperative prioritizes Education and Training as a strategy to improve members' welfare. Methodology/approach: A quantitative approach using structural equation Modeling (SEM) with Partial Least Squares (PLS) was applied to 100 randomly selected members who attended education and training programmes. Results: Cooperative Education significantly improved member welfare (path coefficient = 0.400; p = 0.023), while entrepreneurship training showed no significant effect (p = 0.136). This suggests that training programs are less effective because they are not sufficiently relevant or practical in the real world. Additional analysis indicates that education fosters better financial literacy and greater cooperative participation, thereby indirectly strengthening social capital and economic resilience among members. Conclusions: Enhancing education quality and designing more adaptive, practice-oriented training are essential to strengthen member welfare. These findings show that the training carried out by cooperatives has not significantly improved members' welfare. This may be due to the fact that the training was theoretical, less applicable, and not followed by continuous mentoring. Limitations: This study is limited to education and training variables; the sample of respondents is 100 due to limited research time and resources. Contributions: The findings highlight the need for continuous improvement in cooperative empowerment programs and serve as evaluation material for administrators.